2006
DOI: 10.1161/01.hyp.0000203772.78696.67
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid Receptor Antagonism Attenuates Cardiac Hypertrophy and Failure in Low-Aldosterone Hypertensive Rats

Abstract: Abstract-Chronic elevation of plasma aldosterone contributes to heart failure. Mineralocorticoid receptor (MR) antagonism is cardioprotective in such a setting, but whether such protection occurs in the presence of low-aldosterone concentrations remains unclear. We investigated whether MR blockade attenuates cardiac hypertrophy and failure in rats with salt-sensitive hypertension. Dahl salt-sensitive (DS) rats fed a high-salt diet from 7 weeks develop concentric left ventricular (LV) hypertrophy secondary to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
178
2
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 206 publications
(210 citation statements)
references
References 48 publications
22
178
2
8
Order By: Relevance
“…37 Cardiac fibrosis is a pathological feature associated with hypertension and cardiac hypertrophy and is responsible for LV diastolic dysfunction, likely as a result of an increase in LV stiffness. 25 In this study, LV hypertrophy and fibrosis were markedly attenuated by LOS in the presence of a moderate reduction in blood pressure, consistent with our previous results and those of others. 10,22,38 Thiazide-like diuretics have been the cornerstone of hypertension treatment for several years.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…37 Cardiac fibrosis is a pathological feature associated with hypertension and cardiac hypertrophy and is responsible for LV diastolic dysfunction, likely as a result of an increase in LV stiffness. 25 In this study, LV hypertrophy and fibrosis were markedly attenuated by LOS in the presence of a moderate reduction in blood pressure, consistent with our previous results and those of others. 10,22,38 Thiazide-like diuretics have been the cornerstone of hypertension treatment for several years.…”
Section: Discussionsupporting
confidence: 93%
“…NM_022456) receptor, transforming growth factorb1 (TGF-b1) 22 or connective tissue growth factor (CTGF). 25 Reagents for detection of human 18S rRNA (Applied Biosystems) were used to quantify rat 18S rRNA as an internal standard.…”
Section: Quantitative Rt-pcr Analysismentioning
confidence: 99%
“…We confirmed that the serum concentration of aldosterone did not increase in the DS+HS group compared with that of the DS+NS group. Recent basic studies have demonstrated that MR activation is important in the etiology of cardiovascular and renal diseases not only in highaldosterone status but also in low-aldosterone hypertension, 12,36 which are consistent with our results. How is MR activated in lowaldosterone hypertension?…”
Section: Discussionsupporting
confidence: 93%
“…7,8 Recent large clinical trials, both the Randomized Aldactone Evaluation Study (RALES) and Eplerenone Post-Acute Myocardial Infarction Heart Failure Efficacy and Survival (EPHESUS) studies, and other animal studies have demonstrated the beneficial effects of mineralocorticoid receptor (MR) antagonists on the prognosis and ventricular remodeling. [9][10][11][12] However, little is known about the effects of the MR antagonist on atrial remodeling in hypertension. MR stimulation is linked to interstitial fibrosis, inflammation, hypertrophy and superoxide production in the heart, [13][14][15] all of which are known to provide a pathogenic substrate for AF.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous reports have demonstrated that expression of MR mRNA was significantly increased under pathological conditions, such as post-MI and heart failure (47,48). Indeed, in vitro studies have shown that aldosterone and α-adrenergic stimulation each significantly increases the expression of MR mRNA (49,50).…”
Section: Discussionmentioning
confidence: 92%